Sodium Fluorescein-Guided Gross Total Resection of Pediatric Exophytic Brainstem Glioma: 2-Dimensional Operative Video. Issue 2 (12th December 2020) - Markosian, Christopher; Mazzola, Catherine A; Tomycz, Luke D
Abstract: Brainstem gliomas comprise 10% to 20% of pediatric intracranial tumors. 1 Gross total resection is associated with the greatest long-term survival. 1 However, due to the eloquence of surrounding brain tissue, an aggressive resection is not always achievable and can be associated with significant risk. 2 Sodium fluorescein can be used to help differentiate between tumor and normal tissue. 3, 4 In this operative video, we demonstrate the step-by-step technique to utilize fluorescence in surgically resecting an exophytic glioma arising from the midbrain in a 16-yr-old male. Technical nuances are highlighted in this operative video, including the use of the YELLOW 560 (Zeiss) filter to differentiate fluorescent tumor from normal tissue as well as strategic splitting of the tentorium to expose the supratentorial component of the tumor. A decrease in motor potentials of the right leg during the case did not translate into neurological worsening postoperatively; at 3-mo follow-up, the patient attests to better strength and coordination on his affected side. In summary, sodium fluorescein can be used as a critical adjunctive tool for successful surgery in the case of a brainstem tumor. Alternatives to this procedure included gross total resection with 5-aminolevulinic acid, subtotal resection with chemotherapy, and active monitoring, but were not chosen due to their limitations in this clinical case. 5-7  Appropriate patient consent was obtained to perform this procedure and present this clinical case and surgical video for academic purposes.